Isoxazolidine-fused meso-tetraarylchlorins as key tools for the synthesis of mono- and bis-annulated chlorins1. Issue 26 (14th July 2015) - Aguiar, António; Leite, Andreia; Silva, André M. N.; Tomé, Augusto C.; Cunha-Silva, Luís; de Castro, Baltazar; Rangel, Maria; Silva, Ana M. G.
<x xml:space="preserve">Abstract</x> An efficient synthetic approach to prepare novel annulated chlorin derivatives, a meso-tetraarylchlorin bearing an azepine ring and another bearing simultaneously an azepine and a 2H-pyran ring, is described.